The Behaviour of Pig Breeders to Concerning of Waste Treatment at Puhu Village, Payangan District, Gianyar Regency - I M., Pri Setiawan; Suparta, I N.; Tatik Ingriati, N. W. (Jurnal Peternakan Tropika, 2018)
Pig waste that is not handled properly can be one of the triggers of environmental pollution. Behavior of pig breeders to date has not efficiently processed the waste product. The condition occurs because of lack of care for breeders on how to properly handle the waste. This study aimed to find out the behavior of breeder concerning pig waste treatment at Puhu Village, Payangan District, Gianyar Regency .  The location was chosen Purposive with the reason that Puhu Village is a tourist village whose waste processing is not good yet. Respondents were determined by Quota Purposive Sampling, the number of respondents as many as 35 of pig breeders, five respondents for each dusun with the total number seven dusun at Puhu Village. Primary data were obtained from direct interviews and observations and secondary data were obtained from data recording in the Puhu Village Office. This study conducted from May till July 2018 at Puhu Village, Payangan District, Gianyar Regency. Data analysis in used by means of qualitative descriptive and Spearman level correlation coefficient test. The results showed that the behavior of breeder concerning pig waste treatmens is in medium category. The factors related to the behavior of breeder in pig waste treatmens such as age and number of livestock ownership have a non-significant corelation (P> 0,01). While education, building ownership, percepion, and motivation has avery significant corelation (P< 0,01)) with behavior of breeder in pig waste treatment. Sugestions that can be conveyed to the government is more active in providing counseling and training to breeders on the processing of pig waste. Breeders in order to increase their perception and motivation in processing pig waste through counseling assistance to minimize environmental pollution.   Keywords: Behavior, Pig breeder, waste treatment